PERTANGGUNG JAWABAN PEJABAT PEMBUAT AKTA TANAH (PPAT) DALAM PEMBUATAN AKTA JUAL BELI DENGAN MENGGUNAKAN BLANGKO KOSONG (STUDI PUTUSAN MAHKAMAH AGUNG NOMOR 2082 K/PDT/2017) - Fahreza, Redy Farhan; Purba, Hasim; Sutiarnoto, Sutiarnoto (Law Jurnal, 2024)
Population growth and economic development in Indonesia have encouraged an increase in land sale and purchase transactions, accompanied by the need for legal certainty. In this context, the Land Deed Official (PPAT) plays an important role in the preparation of authentic deeds relating to the transfer of land rights. However, in the field, there are several problems, one of which is the use of blank forms, which became the subject of a case in Supreme Court Decision Number 2082 K/PDT/2017.This research aims to analyze the authority of PPAT regarding the use of blank forms, as well as their responsibility for errors that occur based on the decision. In addition, this research also explores legal protection for the injured party. The method used is normative juridical with an analytical descriptive approach. In this study, researchers collected primary legal materials in the form of laws and regulations and Supreme Court Decision No. 2082 K/PDT/2017, as well as secondary legal materials in the form of legal literature and tertiary legal materials as support. Data collection is carried out through literature study, which is then analyzed qualitatively to answer problems related to the authority and responsibility of PPAT.The results showed that the PPAT's action in signing the sale and purchase deed with a blank form is against the law and is not in accordance with the applicable regulations in Indonesia. This action can result in a change in the status of the deed from an authentic deed to a deed under the hand. Offending PPATs may be subject to sanctions of dishonorable dismissal and are required to pay compensation to the injured party. Although PPATs have the responsibility to prepare the blanks, they are still required to follow established procedures, including reading out the contents of the deed in the presence of all parties, to ensure that they understand and agree to the contents of the deed.